Creativity and Academic Achievement of Secondary School Students of District Yamuna Nagar: Analyzing the Relationship between Creativity and Academic Achievement in District Yamuna Nagar (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Study of creativity and academic achievement of secondary school students has been examined in this paper. The sample consisted of 100 students of secondary school students of district Yamuna Nagar. The t-test was applied to find the key insights.